The Holy Spirit-- in biblical teaching, through the centuries, and today - Thiselton, Anthony C. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2013)
"This learned book by eminent scholar Anthony Thiselton is a detailed biblical, historical, and contemporary study of the Holy Spirit. Thiselton presents an up-to-date account of biblical teaching on the topic, including exposition of passages and hermeneutics; offers a comprehensive historical survey from the Apostolic Fathers to Jonathan Edwards; and engages a host of modern theologians. In the last part of his book Thiselton discusses a remarkably wide range of writings on the Holy Spirit from the nineteenth century to the present day. He interacts explicitly with Pentecostals and the Renewal Movement in a sympathetic, positive, yet critical manner. The book as a whole is at once scholarly and readable, comprehensive and practical. The Holy Spirit -- in Biblical Teaching, through the Centuries, and Today offers scholarly work on specific themes such as prophecy, tongues, the miraculous, the range and nature of the Spirit's gifts, and the Holy Spirit in relation to the Trinity, along with practical consequences for worship and life."--Publisher's website.
The Holy Spirit in Biblical Teaching -- The Spirit of God in the Old Testament -- The Spirit in Judaism -- The Holy Spirit in the synoptic gospels -- The Holy Spirit in Acts -- Key themes in Paul -- Further gifts of the Spirit and more controversial themes that involve hermeneutics -- The Holy Spirit, the paraclete, in the Johannine writings -- 1 and 2 Peter, Hebrews, James, Jude, and Revelation -- The Holy Spirit through the Centuries -- The apostolic fathers and early Christian apologists -- The ante-Nicene fathers -- The post-Nicene Western fathers -- The post-Nicene Eastern fathers -- The earlier medieval period -- The later Middle Ages : from Bonaventura and Aquinas to Julian of Norwich and Walter Hilton -- The major reformers -- The seventeenth and eighteenth centuries : from Owen to Edwards -- The Holy Spirit in Modern Theology and Today -- The nineteenth century : the parting of the ways -- The earlier part of the twentieth century -- The later twentieth century to 1985 -- Three pentecostal or renewal New Testament scholars : Fee, Stronstad, and Turner -- Five major theologians : Congar, Moltmann, Pannenberg, Lossky, and Zizioulas -- Other writers from the end of the century : 1986-2000 -- The twenty-first century -- Summary, conclusions, mutual dialogue, and personal reflections.
Includes bibliographical references (pages 501-521) and indexes.
Keywords: Holy Spirit; Holy Spirit; Holy Spirit -- History of doctrines